Resource Misallocation in Turkey - Nguyen, Ha (World Bank, Washington, DC, 2016)
This paper examines resource misallocation within narrow industries in Turkey. It finds that resource misallocation in Turkey is substantial. The hypothetical gain from moving to "U.S. efficiency" is 24.5 percent of manufacturing total factor productivity in 2014. The evolution of resource misallocation over time and across disaggregated sectors is also examined. Improvement in allocative efficiency was sizable between 2003 and 2013, but significantly slower after 2007. However, the earlier trend reversed in 2014 and resource misallocation worsened in Turkey's manufacturing. The cross-sector analysis reveals that misallocation is most pronounced in textiles, transport, food, and leather.